The Effects of Stress Management Intervention on Freshman Students’ Academic Stress and Coping Strategies - De Guia, Glenda (Journal of Education and Society, 2018)
This study examined the effects of DEAL-Based intervention on freshman students’ academic stress and coping strategies. A longitudinal design was adopted using quantitative method on the 91 freshman students of Northern Samar. A total of 754 freshman students from the clustered state universities and colleges in the province of Northern Samar were included in the pretest. Among those who participated in the pretest only 296 qualified the inclusion criteria, only 96 students attended the intervention program, and only 91 freshman students completed the post-intervention tests. Academic stress and coping strategies were measured by students stress inventory, and brief coping orientation of problem experienced (Brief COPE). MANOVA was used to determine the significant difference between the pretest and posttest on academic stress and the three coping strategies of the respondents. ANOVA repeated measures was used to determine the significance and the effect of the intervention across 5-time interval pretest and posttest assessments. DEAL-based intervention is very effective in lessening the academic stress of the students including those with severe academic stress. The intervention has positive effects on the coping strategies of the respondents.